Boron and pyridinic nitrogen-doped graphene as potential catalysts for rechargeable non-aqueous sodium–air batteries. Issue 36 (9th June 2020) - Benti, Natei Ermias; Tiruye, Girum Ayalneh; Mekonnen, Yedilfana Setarge
Abstract : We performed density functional theory analysis of heteroatom doped graphene as potential catalysts for rechargeable non-aqueous sodium–air batteries. Pyridinic nitrogen and boron doped graphene exhibited too low overpotential reaction pathways. Abstract : In this work, we performed density functional theory (DFT) analysis of nitrogen (N)- and boron (B)-doped graphene, and N, B-co-doped graphene as potential catalysts for rechargeable non-aqueous sodium–air batteries. Four steps of an NaO2 growth and depletion mechanism model were implemented to study the effects of B- and N-doped and co-doped graphene on the reaction pathways, overpotentials, and equilibrium potentials. The DFT results revealed that two-boron- and three-nitrogen (pyridinic)-doped graphene exhibited plausible reaction pathways at the lowest overpotentials, especially during the charging process (approximately 200 mV), thus, significantly improving the oxygen reduction and oxidation reactions of pristine graphene. In addition, pyridinic nitrogen-doped graphene meaningfully increased the equilibrium potential by approximately 0.30 eV compared to the other graphene-based materials considered in this study. This detailed DFT study provides valuable data that can be used for the successful development of low-cost and efficient graphene-based catalysts for sodium–air battery systems operating with non-aqueous electrolyte.